2012
DOI: 10.1007/s00284-012-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Antagonistic Bacillus Strains Capable to Degrade Ethylenethiourea

Abstract: In this study, more than 150 bacteria showing antagonistic properties against bacterial and fungal pathogens of the tomato plant were isolated and characterized. The most efficient agents against these phytopathogenic microorganisms belong to the genus Bacillus: the best biocontrol isolates were representatives of Bacillus subtilis, B. mojavensis and B. amyloliquefaciens species. They intensively produced fengycin or/and surfactin depsipeptide antibiotics and also proved to be excellent protease secretors. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…A preliminary taxonomic identification, extracellular enzyme and antibiotic secretion characteristics, and a wide in vitro antagonistic spectrum of strain SZMC 6179J were reported previously (Vágvölgyi et al 2013). Strain SZMC 6179J produces surfactins and fengycins, and it is effective against Xanthomonas vesicatoria and a wide set of phytopathogenic filamentous fungi (Manczinger et al 2011; Szekeres et al 2013; Vágvölgyi et al 2013). …”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…A preliminary taxonomic identification, extracellular enzyme and antibiotic secretion characteristics, and a wide in vitro antagonistic spectrum of strain SZMC 6179J were reported previously (Vágvölgyi et al 2013). Strain SZMC 6179J produces surfactins and fengycins, and it is effective against Xanthomonas vesicatoria and a wide set of phytopathogenic filamentous fungi (Manczinger et al 2011; Szekeres et al 2013; Vágvölgyi et al 2013). …”
Section: Introductionmentioning
confidence: 57%
“…Strain SZMC 6179J was identified in a previous study (Vágvölgyi et al 2013) as Bacillus subtilis by the sequence analysis of a fragment of the gyrA gene (Genbank accession number: JX683908) according to Reva et al (2004). Phylogenetic analysis by the MLST approach performed with the full sequences of nine genes ( gyrA, gyrB, purH, glpF, pycA, ilvD, rpoD, tpiA and pta ) revealed that strain SZMC 6179J is belonging to the B. subtilis subsp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that surfactin, iturin and fengycin A are major CLP components that exert antimicrobial activities (6,1719). In the present study, the extracts purified from the B. amyloliquefaciens JN68 strain were confirmed to be surfactin, iturin and fengycin A.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the three major CLPs that are known to possess antimicrobial activities are surfactin, iturin and fengycin A. Previous studies have demonstrated that surfactin, iturin and fengycin A possess antifungal and antibacterial activities (6,1719). Notably, CLPs have several advantages, including low toxicity, high biodegradability and environmentally positive characteristics (2023).…”
Section: Introductionmentioning
confidence: 99%